Evidence of Microbial Activity in Coal Seam Production Water and Hydrochemical Constraints - Yuan Bao; Xueru Chen; Zhidong Guo; Zhengyan Li; Yufei Zhuang; Min Gao (Energies)
This study aims to explore microbial activity evidence, composition of archaeal communities, and environmental constraints in coalbed-produced waters from the Hancheng Block, a representative region for coalbed methane development on the eastern margin of Ordos Basin, China. The investigation involves analyzing microbial community composition using 16S rRNA sequencing analysis as well as examining hydrogeochemical parameters. The results indicate that Euryarchaeota and Thaumarchaeota are predominant phyla within archaeal communities present in coalbed-produced water from the Hancheng Block. Among these communities, Methanobacterium is identified as the most abundant genus, followed by Methanothrix and Methanoregula. Moreover, a positive correlation is observed between the abundance of Methanobacterium and the levels of total dissolved solids as well as Mn; conversely, there is a negative correlation with dissolved organic carbon, Zn concentrations, and pH. The abundance of Co and Ni primarily influence Methanothrix while pH and Zn play significant roles in controlling Methanoregula. Additionally, No. 5 coal seam waters exhibit greater species diversity in the archaeal community compared to No. 11 counterparts. The higher abundance of archaea in the No. 5 coal seam promotes biogas generation due to the correlation between bicarbonate and dissolved inorganic carbon isotope. These research findings hold scientific significance in guiding the exploration and development of biogas within coal seams.